A simple spraying process greatly enhanced field emission of novel T-ZnO-supported CNT emitters. Issue 8 (3rd February 2016) - Yang, Zunxian; Yan, Wenhuan; Lv, Jun; Qian, Kun; Zhang, Yuxiang; Liu, Jiahui; Ai, Jingwei; Guo, Tailiang; Chen, Enguo; Hu, Liqin
Abstract : T-ZnO-supported CNT emitters were fabricated by using a simple process involving two spraying steps followed by heat treatment in air. Abstract : T-ZnO-supported CNT emitters were fabricated by using a simple process involving two spraying steps followed by heat treatment in air. The T-ZnO-supported CNT emitter was observed to form a particular architecture with the T-ZnO support containing a vertically aligned CNT emitter firmly attached to the electrode. These particular T-ZnO-supported carbon nanotube emitters displayed good contacts with the substrate, vertically aligned CNT emitters and density-controllable T-ZnO supports, which all appear to explain the excellent field emission performance of the electrode. Of the materials tested, the T-ZnO-supported CNT emitters exhibited the best field emission capability, i.e., the lowest turn-on electrical field, with a value of 0.96 V μm −1 at a current density of 0.01 mA cm −2, and the highest field enhancement factor, with a value of 13 883, as well as good emission stability, with only ∼18% of the current attenuated over an operating span of ∼200 min. These characteristics indicate that the T-ZnO-supported CNT emitters constitute a very promising cathode material candidate for field emission.